Knowledge, Attitude and Practices of Skilled Birth Attendants towards Immediate Postpartum Family Planning Services - Shazia Nasim Akbani; Sarah Saleem (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: Postpartum Family Planning (PPFP) is one of the "High Impact Practices" to reduce maternal and infant mortality in Low and Middle-Income Countries (LMICs). Health Service Providers (HSPs) need to integrate these services as a core component of maternity services. This study aims to evaluate HSPs' "knowledge, attitude and practices" regarding immediate PPFP. Method: A descriptive, cross-sectional study carried out in ten public sector secondary and tertiary hospitals in Karachi, Pakistan. Study participants were accredited Skilled Birth Attendants (SBAs) including doctors and nurse/midwives. Results were analyzed using "Statistical Package of Social Sciences (SPSS) version 19". Results: A total of 237 SBAs were interviewed of which 141(59%) were doctors and 96(41%) were nurses/midwives. Almost equal percentage of doctors and nurses/midwives were knowledgeable about PPFP. Out of the total, 72% SBAs (107 doctors and 63 nurse/midwives) were presently providing PPFP service. Supportive attitude towards PPFP was shown by 79(56%) doctors and 34 (35%) nurses/midwives. Nearly 30% of SBAs had misconception that religion prohibits FP practices. Of those who were not practicing PPFP the main reasons were time constraint and fear of introducing medical complication. Interestingly 30% of nurses/midwives were not allowed by the Head of the Obstetric Units to practice these services thus missing on the available resources for task sharing.  Conclusion: PPFP should be mandatory component of maternity care and ongoing efforts are required for knowledge enhancement and behavior change of HSPs. Policy changes are also needed to decrease impediments at the PPFP service delivery level.